2018
DOI: 10.24912/jm.v22i2.359
|View full text |Cite
|
Sign up to set email alerts
|

Capital Market Integration In Some Asean Countries Revisited

Abstract: Financial market integration in Southern Asia especially in ASEAN main member countries still attractive to scrunitized. Most of these countries were devastated during severe regional financial crisis in 1997 but global financial crisis in 2008 have different impact toward these countries. The finding shows that comovement were exist among Indonesia, Malaysia, Singapore and Thailand’s capital market during January 1997 to December 2013 period. Comovement still exist during post Asian financial Crisis 1997 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 12 publications
(29 reference statements)
1
11
0
7
Order By: Relevance
“…The underlying reason was that the stock markets in Asia had proven to have a high correlation and were integrated. It was supported by researches such as by Click and Plummer (2005), Karim and Karim (2012), Karim and Ning (2013), Robiyanto and Ernayani (2018), Suganda and Soetrisno (2016), Suganda and Hariyono (2018), Surianshah, Karim, and Khalid (2017). Hence, the implementation of the OGARCH model for Asian stock markets is very feasible.…”
Section: Introductionmentioning
confidence: 96%
“…The underlying reason was that the stock markets in Asia had proven to have a high correlation and were integrated. It was supported by researches such as by Click and Plummer (2005), Karim and Karim (2012), Karim and Ning (2013), Robiyanto and Ernayani (2018), Suganda and Soetrisno (2016), Suganda and Hariyono (2018), Surianshah, Karim, and Khalid (2017). Hence, the implementation of the OGARCH model for Asian stock markets is very feasible.…”
Section: Introductionmentioning
confidence: 96%
“…In the period after the Asian financial crisis, Suryanta (2011) found consistencies with the findings of Palac-McMiken (1997), Kim and McKenzie (2008), and Roca et al (1998). However, Robiyanto and Ernayani (2018) found relatively different results, where after the Asian financial crisis, the Indonesian capital market actually had the same movement Economies 2021, 9, 141 2 of 9 (co-movement) as the capital market in ASEAN countries. Meanwhile, Muharam et al (2020) measured the degree of integration of capital markets in Asia using the Orthogonal GARCH approach, and found that the Indonesian, Philippine, and Malaysian capital markets were the capital markets that were segmented and were not integrated with the capital markets in Asia.…”
Section: Introductionmentioning
confidence: 93%
“…They even detected a reciprocal relationship between the two. Meanwhile, Robiyanto and Ernayani (2018) showed that there was an interdependence between local and world capital markets as measured using the DJIA index indicator. Antoniou, Pescetto, and Stevens (2007) found that the condition of the American capital market was such a global factor that affected both the established and the emerging market.…”
Section: Background Of the Studymentioning
confidence: 99%